2020
DOI: 10.2320/matertrans.p-m2020835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weld Line Direction on Tensile Deformation Behavior —Development of Forming Technology for Tailor-Welded Blank Application 2nd Report—

Abstract: The stretch flangeability of tailor-welded blank depends on the angle between weld line and the tangential line of blank edge, which is generally the tensile direction in stretch flanging. This effect was studied by uniaxial tensile testing of tailor-welded high-strength-steel specimens with a weld line at 45, 60, or 90 degrees from the tensile direction. The 60-degree-weld-line specimen provides the highest elongation at the maximum load. This is the angle at which the strain component in the weld-line direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Concerning the orientation of the weld line, data showed that the springback of longitudinally welded samples is similar to that of specimens made of homogeneous materials [14,15], unlike cross-welded samples where springback decreased by about 44% in the thinner material area. The springback for thicker material is similar to one of the samples made of homogeneous material.…”
Section: Introductionmentioning
confidence: 85%
“…Concerning the orientation of the weld line, data showed that the springback of longitudinally welded samples is similar to that of specimens made of homogeneous materials [14,15], unlike cross-welded samples where springback decreased by about 44% in the thinner material area. The springback for thicker material is similar to one of the samples made of homogeneous material.…”
Section: Introductionmentioning
confidence: 85%